Extramammary Paget Disease: A Review - Farishta Khan; Shweta Karakara; Zhenghao Wang; Honey Frimpong-Manso; Birgitta van Bodegraven; Jane Sterling; Paul Craig; Andrew Nordin; Zoe C Venables (Clinical and Experimental Dermatology, 2026)
Abstract Extramammary Paget disease (EMPD) is defined by the World Health Organisation (WHO), as ‘a rare adenocarcinoma characterized by a predominant intraepithelial growth of neoplastic cells originating in the skin (primary EMPD) or representing intraepithelial spread of an underlying visceral carcinoma (secondary EMPD)’(1).It affects areas rich in apocrine glands, such as genital and perianal skin. First described by Radcliffe Crocker in 1889, EMPD often remains confined to the epidermis for years, following a quiescent course. Diagnosis is frequently delayed or missed due to its insidious onset and non-specific symptoms, which can mimic other inflammatory dermatoses. Importantly, EMPD is linked to underlying visceral malignancies although the risk varies anatomically. Data from England on EMPD incidence and 5-year survival from 2013 to 2020 shows crude incidence rate of 0.17 per 100,000 person-years (PY). Additionally, the 5-year net survival for EMPD diagnosed in 2013 was 90.9%. The reported net survival for EMPD is comparable to melanoma (89.6%), prostate (85.8%) and breast cancers (85.9%) overall i.e. for all stages combined. Management of EMPD focuses on identifying and addressing any associated underlying malignancies. Other treatment options include surgery or topical treatments, while non-surgical approaches such as radiotherapy and systemic treatment are used for advanced or metastatic disease. Treatment approaches may not be curative and recurrence rates can be up to 50%, highlighting the importance of close surveillance. This review covers EMPD’s history, classification, epidemiology, aetiology, pathogenesis, diagnosis and highlights current strategies for malignancy screening and patient management. These findings are important as they contribute to our understanding of the trends and outcomes of this rare disease.